More Dependent Types - Chlipala, Adam (Certified Programming with Dependent Types, 2013)
This chapter contains sections titled: 8.1 Length-Indexed Lists, 8.2 The One Rule of Dependent Pattern Matching in Coq, 8.3 A Tagless Interpreter, 8.4 Dependently Typed Red-Black Trees, 8.5 A Certified Regular Expression Matcher